Alameda Integración Urbana Barbosa - Santander (2023)
Currently the municipality of Barbosa does not have enough recreational urban area for its population. This makes urban activities monotonous and creates an attitude of indifference between social and cultural relations in the community. Currently, public spaces of a recreational nature have not been created for the population, which today is close to 30 thousand inhabitants.